Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Pegawai Sekretariat DPRD Kabupaten Kutai Timur - Mihani . (Sekolah Tinggi Ilmu Ekonomi STEMBI Bandung, 2018)
Tujuan_ This study tries to identify to what extent competence, discipline, motivation, work environment, and leadership of staff DPRD secretariat it will also identify which factors give the most impact toward staff performance. Desain/Metode_ Analysis model used to prove hypothesis is model analysis multiple linier regression that be analysed with using statistics computer program package, that is SPSS v. 20.0 for Windows. Responden that becoming objective this research are counted 113 of staff DPRD secretariat. Temuan_ Result of statistics analysis show that coefficient of the free variables regression, that is involvement factor in competence = 0,044, discipline = 0,111, motivation = 0,055, work environment = 0,023, leadership = 0,730, and constanta equal to 0,262. Equation of multiple linier regression is : Y = 0,262 + 0,044X1 + 0,111 X2 + 0,055 X3 + 0,023 X4 + 0,730X5. Conclusion that receive that level of influence explained by competence, discipline, motivation, work environment, leadership as independent variable impact toward performance of staff DPR secretariat are equal to correlation coefficient, that is 0,867 and level of depended performance to fifth of free variables above is equal to determination coefficient value that is 0,752 or 75,2 %. Result of analysis F – test indicate that all free variables by together have significant influence toward performance of staff DPRD secretariat. By parsial, variable competence, motivation, work environment have not significant influence to performance of staff DPRD secretariat. Variable discipline and leadership have significant. Variabel independent has dominant influence to performance of sfaff DPRD secretariat is leadership. Implikasi_ This research excepted to benefit to all side, especially for institution head to dig elements that increasing performance of staff DPRD secretariat in Kutai Timur Regency. Tipe Penelitian_Empirical Study